The potential of biomarkers for diagnosing insomnia: Consensus statement of the WFSBP Task Force on Sleep Disorders - Dikeos, Dimitris; Wichniak, Adam; Ktonas, Periklis Y; Mikoteit, Thorsten; Crönlein, Tatjana; Eckert, Anne; Kopřivová, Jana; Ntafouli, Maria; Spiegelhalder, Kai; Hatzinger, Martin; Riemann, Dieter; Soldatos, Constantin (The world journal of biological psychiatry, 2023)
OBJECTIVES: Thus far, the diagnosis of insomnia is based on purely clinical criteria. Although a broad range of altered physiological parameters has been identified in insomniacs, the evidence to establish their diagnostic usefulness is very limited. Purpose of this WFSBP Task Force consensus paper is to systematically evaluate a series of biomarkers as potential diagnostic tools for insomnia. METHODS: A newly created grading system was used for assessing the validity of various measurements in establishing the diagnosis of insomnia; these measurements originated from relevant studies selected and reviewed by experts. RESULTS: The measurements with the highest diagnostic performance were those derived from psychometric instruments. Biological measurements which emerged as potentially useful diagnostic instruments were polysomnography-derived cyclic alternating pattern, actigraphy, and BDNF levels, followed by heart rate around sleep onset, deficient melatonin rhythm, and certain neuroimaging patterns (mainly for the activity of frontal and pre-frontal cortex, hippocampus and basal ganglia); yet, these findings need replication, as well as establishment of commonly accepted methodology and diagnostic cut-off points. Routine polysomnography, EEG spectral analysis, heart rate variability, skin conductance, thermoregulation, oxygen consumption, HPA axis, and inflammation indices were not shown to be of satisfactory diagnostic value. CONCLUSIONS: Apart from psychometric instruments which are confirmed to be the gold standard in diagnosing insomnia, six biomarkers emerge as being potentially useful for this purpose.
Keywords: biomarkers; poruchy iniciace a udržování spánku; psychometrics; Sleep; spánek; systém hypofýza - nadledviny; Sleep Initiation and Maintenance Disorders; grading system; Humans; biologické markery; Insomnia; diagnostic accuracy; lidé; Pituitary-Adrenal System; Hypothalamo-Hypophyseal System; Biomarkers; systém hypotalamus-hypofýza